Pengaruh Promosi Dan Citra Merek Terhadap Keputusan Pembelian Air Minum Kemasan Cup CV. Tirta Sasmita Kota Tangerang Selatan - Nugraha, Alwan; septiani, Fauziah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to determine the extent to which promotion and brand image influence the purchasing decisions of CV. Tirta Sasmita’s cup-packaged drinking water. This research uses a quantitative approach with a population of 96 consumers who have purchased and consumed Tirta Sasmita cup drinking water. The sampling technique used is purposive sampling, which involves selecting respondents based on specific criteria such as gender and age. The data analysis process includes instrument testing (validity and reliability), classical assumption tests (normality, multicollinearity, and heteroscedasticity), linear regression analysis, correlation coefficient tests, coefficient of determination, and hypothesis testing using t-tests and F-tests. The results show that the coefficient of determination is 0.312, meaning that promotion and brand image contribute 31.2% to purchasing decisions, while the remaining 68.8% is influenced by other variables not examined in this study. The partial t-test indicates that the promotion variable has a t-value greater than the t-table (5.165 > 1.661) with a significance value of 0.000 < 0.05. The brand image variable also shows a t-value greater than the t-table (5.943 > 1.661) with a significance value of 0.000 < 0.05.Furthermore, the F-test results demonstrate that promotion and brand image simultaneously have a positive and significant effect on purchasing decisions, as evidenced by the F-value being greater than the F-table (21.091 > 3.09) with a significance level of 0.000 < 0.05. Keywords: Promotion, Brand Image, Purchase Decision